Efecto de la cáscara sobre el mecanismo de endurecimiento del frijol común (Phaseolus vulgaris): resultados preliminares - de León, L. F.; Bressani, R.; Elías, L. G. (Agronomía Mesoamericana, 2016)
Samples of cotyledons and whole black beans (Phaseolus vulgaris, Tamazulapa variety) were stored for 6 weeks at 37°C and 90% relative humidity conditions in order to establish the chemical and physical changes and the role of the seed coat in the hard-to-cook phenomena. After the storage period, samples of whole beans were divided In two sub-samples: one with the and other without the seed coat. These two samples and the cotyledons were analyzed forcooking time, water absorption, dietary fiber, tanic acid, soluble pectins and phytic acid. Cooking time of whole beans Increased from 99 to 480 minutes; for the cotyledons, this value Increased from 45 to 111 minutes. Cooking time of the dehulled bean, stored as a whole bean, increased from 45 to 103 minutes. Water absorption in whole beans and cotyledon decreased, although In cotyledons this was higher. No changes were observed in the dietary fiber content of the cotyledons and the beans dehulled after storage. However, in the whole grains neutral -detergent fiber decreased, while acid detergent fiber, cellulose and lignin did not have a significant change. On the other hand, soluble pectates decreased In the whole bean and cotyledon; tannin content as tanic acid decreased only In the whole beans. The data obtained suggest that the seed coat could play a significant role in the hard-to-cook effect before and during storage